CORAL REEF CULTIVATION AT PT. SRI KANDI AQUARIUM, BANYUWANGI: ANALYSIS OF STAGES AND RESULTS OF TRANSPLANTATION of Acropora formosa, Acropora granulosa, and Euphyllia glabrescens - Bunayya, Faiq Hanif; Yuniardhi, Dimas Indra; Satria, Rizal Surya; Rahmatulloh, Alfariz Alif; Pardede, Maria Agustina (Universitas Mataram, 2025)
Indonesia is a region known for its abundant natural resources, such as coral reefs. Coral reef ecosystems in Indonesia have begun to decrease, it was recorded that 35.15% of coral reefs in Indonesia entered into poor status or declared damaged. This is due to several factors such as damage caused by the illegal trade of coral reefs carried out by unscrupulous entrepreneurs because of the illegal trade of coral reefs, knowledge and skills are needed regarding transplantation methods in the cultivation of A. formosa, A. granulosa and E. glabrescens to find out the stages and results of transplantation methods in coral reef cultivation. This study was conducted at PT Sri Kandi Aquarium, Banyuwangi Regency, East Java on June 24, 2024 until August 24, 2024. The primary data collection methods used include observation and active participation, while for secondary data using literature studies. The transplantation process in coral reef cultivation consists of several activities, namely the preparation of transplantation tools and materials, making transplantation media, cutting parent fragments, transplantation, maintenance and harvesting. The results of transplantation are then classified based on sizes S, M, L and XL. Thus the transplantation method can be carried out in coral reef cultivation which consists of several stages including preparation of transplantation tools and materials, making transplantation media, cutting coral fragments, attaching the results of cutting fragments to the substrate, sowing corals on the transplantation table under the sea and periodic monitoring and maintenance of corals. The transplantation results obtained will be categorized based on size, namely S, M, L and XL.